Enhanced Adsorption of Epoxy‐Functional Nanoparticles onto Stainless Steel Significantly Reduces Friction in Tribological Studies. (31st January 2023) - György, Csilla; Kirkman, Paul M.; Neal, Thomas J.; Chan, Derek H. H.; Williams, Megan; Smith, Timothy; Growney, David J.; Armes, Steven P.
Abstract: Epoxy‐functional sterically‐stabilized diblock copolymer nanoparticles (ca. 27 nm) are prepared via RAFT dispersion polymerization in mineral oil. Nanoparticle adsorption onto stainless steel is examined using a quartz crystal microbalance. Incorporating epoxy groups within the steric stabilizer chains results in a two‐fold increase in the adsorbed amount, Γ, at 20 °C (7.6 mg m −2 ) compared to epoxy‐core functional nanoparticles (3.7 mg m −2 ) or non‐functional nanoparticles (3.8 mg m −2 ). A larger difference in Γ is observed at 40 °C; this suggests chemical adsorption of the nanoparticles rather than merely physical adsorption. A remarkable near five‐fold increase in Γ is observed for ca. 50 nm epoxy‐functional nanoparticles compared to non‐functional nanoparticles (31.3 vs. 6.4 mg m −2, respectively). Tribological studies confirm that chemical adsorption of the latter epoxy‐functional nanoparticles leads to a significant reduction in friction between 60 °C and 120 °C. Abstract : Introduction of epoxy groups into sterically‐stabilized diblock copolymer nanoparticles leads to their efficient chemical adsorption onto stainless steel whereas the corresponding non‐functional nanoparticles merely undergo physical adsorption. Significantly greater adsorption occurs when the epoxy groups are placed within the steric stabilizer chains, which leads to enhanced lubrication in tribology studies.